The Study of Silviculture System for Selective Cutting and Line Planting (TPTJ) and Indonesian Selective Cutting and Planting (TPTI) Application at PT Intracawood Manufacturing Bulungan Regency, North Kalimantan - M. Taufan; Susilowati, Arida (Talenta Publisher, 2020)
Selective Cutting and Line Planting (TPTJ) silvicultural systems and Indonesian Selective Cutting and Planting (TPTI) are two of the five silvicultural systems that have been determined by the Ministry of Forestry Regulation No. P.11 / Menhut-II / 2009 juncto P.65 / Menhut-II / 2014 concerning silvicultural systems in the area of timber forest product utilization permits (IUPHHK) in production forests. Three other silvicultural systems based on the regulation are the Gap Logging silviculture system, the Fully Made Rejuvenation System, and the Multi Silviculture System. This study aims to examine the implementation of the TPTJ and TPTI systems in the PT Intracawood Manufacturing (PT Intraca) area, Bulungan Regency, North Kalimantan. The methodology of this research is through the approach of growth analysis, comparison of stand increment, observation of environmental conditions, interviews and literature study. Based on the field research, it was found that the diameter increments of Shorea leprosula, Shorea dasyphila, and Shorea parvifolia were greater in the TPTJ system compared to TPTI. However, the TPTI silviculture system at PT Intraca is easier to apply in the field than the TPTJ silviculture system. The TPTJ system has become less effective because planting in the TPTJ system has been carried out by making a 3-meter wide track with a length of approximately 1 km in a plot and if there is potential for the wood to become ineffective. In the area of PT Intraca, to improve the effectiveness of the TPTJ system a mosaic system is used where the planting path is made only in areas with less potential and representative for planting. The types of plants planted in the TPTJ system are far superior, perspective, and are faster than the types of plants in the TPTI system. Planting/enrichment in the TPTI system is easier because it does not need to make a planting path. Planting with seedlings from the extraction is only a transfer from the growth of tillers from areas with an excessive potential for tillers.